Critical infrastructure system security and resiliency - Biringer, Betty E., 1952- (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
'Part l: Security risk assessment. Chapter 1. Introduction to Security Risk Assessment As our nation moves forward in the age of information and global economy, our dependencies on national infrastructure is greater than ever. Compromise of our critical infrastructures could disrupt the functions of our government, business, and our way of life. Catastrophic losses in terms of human casualties, property destruction, economic damages, and loss of public confidence could result from disruptions or degradation in our national infrastructure.'Critical infrastructures are the assets, systems, and networks, whether physical or virtual, so vital to the United States that their incapacitation or destruction would have a debilitating effect on security, national economic security, public health or safety, or any combination thereof' (U.S. Department of Homeland Security 2010). The Homeland Security Presidential Directive 7 (HSPD-7) (U.S. Department of Homeland Security 2010) identified 18 critical infrastructure sectors and a designated federal Sector-Specific Agency to lead protection and resilience-building programs and activities. The sectors include: - Agriculture and Food, - Banking and Finance, - Chemical, - Commercial Facilities, - Communications, - Critical Manufacturing, - Dams, - Defense Industrial Base, - Emergency Services, - Energy, - Government Facilities, - Healthcare and Public Health, - Information Technology, - National Monuments and Icons, - Nuclear Reactors, - Postal and Shipping, - Transportation Systems, and - Water'--
Includes bibliographical references and index.
Keywords: National security -- United States; Public works -- Security measures -- United States; Terrorism -- United States -- Prevention; Infrastructure (Economics) -- United States; Fault tolerance (Engineering)